Predicting common bean (Phaseolus vulgaris) productivity according to Rhizoctonia root and stem rot and weed development at field plot scale - Naseri, Bita; Nazer Kakhki, Seyed Hossein (Frontiers in Plant Science, 2022)
A two-year research trial was conducted to evaluate progression of common bean (Phaseolus vulgaris) growth, Rhizoctonia root rot and weed development in association with productivity when treated with different cultivars, planting dates and weed control methods in north-western part of Iran. To determine the best descriptors, six standard curves were examined to model development of bean dry matter, Rhizoctonia root rot incidence, and weed density during two growing seasons across 256 field plots. Exponential and linear-by-linear models were fitted to bean-disease-weed progression data, and then model parameters representing over-season progress curve elements were used in multivariate regression analyses to estimate bean production. Furthermore, using herbicides (Imazethapyr and Trifluralin) restricted weed density by 28% in early (mid-spring) and 42% in late (late spring to early summer) plantings. Late plantings of two bean cultivars decreased disease progress up to 36% for herbicide use, hand-weeding and control. Although bean dry matter, pod and seed production for herbicide use and hand-weeding treatments were 6-17% greater than control, late planting improved productivity in control by 10-24%. Findings suggested that late planting of bean improved efficiency of herbicides to control weeds. Late planting also restricted Rhizoctonia root rot progress and thus, improved bean yield. There were significant correlations between bean-disease-weed development descriptors. According to principal component analysis, bean-disease-productivity-weed variables accounted for 80% of total data variance. Such information extends our understanding of bean-disease-weed progress in interaction with planting date to develop more effective and sustainable integrated Rhizoctonia management programs.